Investigation of the expression of the C-terminal cross-linking telopeptide of type I collagen (CTXI) in saliva during early and delayed loading of dental implants - Dania Hamid; Shaheen Ahmed; Abdul Hafeez Shaikh; Sadaf Nisar; Raheel Memon; Samreen Malik (BMC Oral Health)
Abstract Background Implants are commonly used as a treatment choice for partially dentate or edentulous patients. Currently, no specific biomarker for assessing the bone status around dental implants of healthy patients has been reported for evaluating bone deposition, resorption, or stability. CTXI (C-terminal telopeptide of type I collagen) is a known specific biomarker for bone resorption. However, CTXI levels in the saliva of healthy patients with dental implants have not been investigated. Objectives This randomized controlled trial aimed to evaluate salivary CTXI levels in dental implant patients with early and delayed loading and to compare them with the values of the periotest to determine implant stability and loading time. Methods This study was conducted in Karachi, Pakistan, and included 40 patients with dental implants placed in the posterior mandible. Patients were randomly divided into two groups based on the timing of implant loading: an early loading group, where implants were functionally loaded within 1 month of placement, and a delayed loading group, where implants were loaded after 3 months. The intervention involved functional loading of the implants according to the assigned group. Implant stability was assessed using a periotest on the day of surgery and at 1 month or 3 months, depending on the group. Additionally, saliva samples were collected from all patients at 1 month and 3 months to evaluate CTXI expression levels using sandwich ELISA. Results A comparison by periotest showed that dental implants were stable in the early loading group and that osseointegration was good; thus, loading could be applied within one month of dental implant placement. However, in our study, the CTXI bone turnover marker was not detected in any group and thus cannot be used to indicate bone implant stability or loading time. Conclusion This study demonstrates that early loading of dental implants can achieve stability and osseointegration within one month, as confirmed by Periotest measurements. However, salivary CTXI levels were undetectable in both early and delayed loading groups, indicating that this biomarker is unsuitable for assessing bone-implant stability or determining the optimal timing for implant loading in healthy patients. These findings suggest further research to explore alternative biomarkers for non-invasive osseointegration and implant stability monitoring. Trial registration Retrospectively registered, ID: NCT06246097, Date of registration: 07/02/2024, ( https://clinicaltrials.gov/ct2/show/NCT06246097 ).